Pengembangan Booklet Inventarisasi Jenis-Jenis Tumbuhan Obat Sebagai Sumber Belajar Biologi Kelas X di Kecamatan Barumun Kabupaten Padang Lawas - Siregar, Laila Khoria; Ulfa, Syarifah Widya (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to develop a booklet based on the local potential of medicinal plants as a learning resource for biology in the biodiversity topic of grade X at SMA Negeri 1 Barumun. The background of this research is rooted in the need for contextual learning media that can connect biology material with students’ surrounding environment, making the learning process more relevant, engaging, and meaningful. The research employed a Research and Development (R&D) method using the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The instruments used included expert validation sheets, teacher and student response questionnaires, and concept comprehension tests. The validation results indicated a very high level of feasibility with expert scores ranging from 95–98%. Practicality testing revealed positive responses from teachers (95%) and students (97%). Furthermore, the effectiveness test through concept comprehension produced an N-gain score of 0.81, categorized as high. These findings demonstrate that the booklet based on the local potential of medicinal plants is not only valid and practical but also effective in improving the quality of biology learning and can serve as an innovative learning resource aligned with 21st-century educational needs.